2022
DOI: 10.3389/fimmu.2022.1017115
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin promotes proliferation of germinal center B cells, formation of plasma cells, and elevated levels of IgG3 anti-dsDNA autoantibodies

Abstract: Systemic lupus erythematosus (SLE) mainly affects females at reproductive age, which has been associated with hormones, such as prolactin (PRL). Different studies suggest that PRL exacerbates the clinical manifestations of SLE both in patients and in mouse models (e.g., the MRL/lpr strain), increasing the production of autoantibodies, which can be deposited as immune complexes and trigger inflammation and damage to different tissues. The objective of this work was to explore the potential mechanisms by which P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…As SLE progresses, there is an increase in production of autoantibodies such as those against double-stranded (ds) DNA 42 . Furthermore, a recent study showed that PRL drives the production of anti-dsDNA autoantibodies in MRL-lpr mice 43 . Whether PRL promotes such autoantibody production by signaling specifically through the LFPRLR was not determined.…”
Section: Resultsmentioning
confidence: 99%
“…As SLE progresses, there is an increase in production of autoantibodies such as those against double-stranded (ds) DNA 42 . Furthermore, a recent study showed that PRL drives the production of anti-dsDNA autoantibodies in MRL-lpr mice 43 . Whether PRL promotes such autoantibody production by signaling specifically through the LFPRLR was not determined.…”
Section: Resultsmentioning
confidence: 99%
“…It should be recalled that physiological role of prolactin, except pregnancy and lactation, is not of great significance comparing to other pituitary hormones. However, it is worth mentioning that prolactin participates in the pathogenesis and activity of several autoimmune disorders ( 38 ), such as for example systemic lupus erythematosus ( 39 ). It should be also mentioned that the single highest values of MBL levels found in our patients with non-compensated hypopituitarism did relate to an individual with three pituitary deficiencies (5891.87 ng/mL) and to another individual with four pituitary deficiencies (4135.07 ng/mL), which is not easy to explain.…”
Section: Discussionmentioning
confidence: 99%